2020
DOI: 10.1038/s41598-020-73867-7
|View full text |Cite
|
Sign up to set email alerts
|

Repeated sampling facilitates within- and between-subject modeling of the human sperm transcriptome to identify dynamic and stress-responsive sncRNAs

Abstract: Epidemiological studies from the last century have drawn strong associations between paternal life experiences and offspring health and disease outcomes. Recent studies have demonstrated sperm small non-coding RNA (sncRNA) populations vary in response to diverse paternal insults. However, for studies in retrospective or prospective human cohorts to identify changes in paternal germ cell epigenetics in association with offspring disease risk, a framework must first be built with insight into the expected biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 111 publications
1
30
0
Order By: Relevance
“…Even as some evidence has confirmed that epigenetic modifications identified in sperm alter offspring development in a meaningful way, the biological mechanism remains unclear for how these epigenetic changes impact offspring development. The prevailing thought is that sncRNA alter the developmental trajectory of the offspring by initiating a cascade of molecular events that propagate the stress signal, shifting the timing of developmental events and guiding development toward a set of neurobiological, physiological, and behavioral traits that are more adaptive in a stressful environment (Morgan et al, 2019(Morgan et al, , 2020; see Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even as some evidence has confirmed that epigenetic modifications identified in sperm alter offspring development in a meaningful way, the biological mechanism remains unclear for how these epigenetic changes impact offspring development. The prevailing thought is that sncRNA alter the developmental trajectory of the offspring by initiating a cascade of molecular events that propagate the stress signal, shifting the timing of developmental events and guiding development toward a set of neurobiological, physiological, and behavioral traits that are more adaptive in a stressful environment (Morgan et al, 2019(Morgan et al, , 2020; see Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Even relatively minor modifications in sperm sncRNA content could shift timing of developmental FIGURE 3 | Hypothesized model of the impact of stress on sperm small non-coding RNA content on developmental trajectories, highlighting the fact that relatively minor changes in sperm small non-coding RNA (as indicated by α1 or α2) could shift the timing of developmental events (e.g., embryo division and implantation) in ways that produce significant differences over time. Reprinted from Morgan et al (2020). Repeated sampling facilitates within-and between-subject modeling of the human sperm transcriptome to identify dynamic and stress-responsive sncRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations